2012
DOI: 10.1002/pd.2945
|View full text |Cite
|
Sign up to set email alerts
|

QF‐PCR: application, overview and review of the literature

Abstract: Quantitative fluorescent polymerase chain reaction has been in diagnostic use in the UK for over 10 years and has proved to be a cost-effective, robust and accurate rapid prenatal test for common aneuploidies. Specific advantages include detection of triploidy, mosaicism and maternal cell contamination. Its application at our centre is described, with developments including stand-alone testing and improvements in strategies for the preparation and testing of chorionic villus biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 39 publications
1
49
1
6
Order By: Relevance
“…In most QF-PCR assays, STR alleles are differentiated from each other by length rather than by name (Mann et al, 2001;Jain et al, 2012;Mann and Ogilvie, 2012). In the present study, we explored the genetic nature of the 11 STR markers and named the alleles according to International Society for Forensic Haemogenetics guidelines (Bär et al, 1997), which may enable the use of these STR markers for other genetic tests such as forensic identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most QF-PCR assays, STR alleles are differentiated from each other by length rather than by name (Mann et al, 2001;Jain et al, 2012;Mann and Ogilvie, 2012). In the present study, we explored the genetic nature of the 11 STR markers and named the alleles according to International Society for Forensic Haemogenetics guidelines (Bär et al, 1997), which may enable the use of these STR markers for other genetic tests such as forensic identification.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, rapid diagnosis of chromosome aneuploidies has been successfully achieved using QF-PCR amplification of chromosome-specific STR markers (Mann and Ogilvie, 2012). STR markers should be highly polymorphic and heterogeneous, and thus more likely to provide informative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QF-PCR has been widely used for the rapid diagnosis of common chromosome aneuploidies in the USA, the UK, and in other European countries (Mann and Ogilvie, 2012). Hills et al (2010) retrospectively analyzed 737 prenatal diagnostic specimens in region 9 of London, and found that 73 cases with serious maternal contamination could be analyzed by QF-PCR alone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that 5% of all human conceptions are aneuploidy (Hassold and Hunt, 2001). Despite the efficiency of karyotyping as a gold standard technique (Shaffer and Bui, 2007), quantitative fluorescent polymerase chain reaction (QF-PCR) has emerged as a rapid, accurate, cost effective, and high throughput method for prenatal diagnosis of chromosomal aneuploidies (Cirigliano et al, 2006;Mann et al, 2008;Mann and Ogilvie, 2012;Rostami et al, 2015). QF-PCR is a PCR-based technique that amplifies short tandem repeats (STRs) located on chromosomes of interest to determine the copy numbers of those chromosomes present per cell (Langlois and Duncan, 2011).…”
Section: Introductionmentioning
confidence: 99%